Konsep Rasionalitas Islami dan Implikasinya terhadap Pengembangan Studi Ekonomi Islam - Ahmad Dimyati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2021)
The study of Islamic rationality is the starting point for the theorizing of Islamic economics. Based on this concept, this article aims to elaborate rationality based on the concepts of classical Islamic thinkers, such as al-Gazali, Ibn Khaldun, Ibn Miskawaih and al-Mawardi. Through a search of their writings, the author intends to reconstruct the original concept of rationality from Islam. Then with the approach used by economic critics, the concept of rationality was expanded. The results of this study indicate that the rigidity of the concept of rationality in the Neoclassical school is undeniable. The behavior of actors in the economy is not only repetitive actions that can be quantified but must be extended as part of the social system. Especially in the concept of Islamic rationality, economic behavior is also closely related to the position of humans as servants of Allah so that they have a spiritual dimension.